Mechanical behaviour of composite calcium phosphate–titanium cranial implants: Effects of loading rate and design. (April 2020) - Lewin, Susanne; Åberg, Jonas; Neuhaus, Dominique; Engqvist, Håkan; Ferguson, Stephen J.; Öhman-Mägi, Caroline; Helgason, Benedikt; Persson, Cecilia
Abstract: Cranial implants are used to repair bone defects following neurosurgery or trauma. At present, there is a lack of data on their mechanical response, particularly in impact loading. The aim of the present study was to assess the mechanical response of a recently developed composite calcium phosphate–titanium (CaP–Ti) implant at quasi-static and impact loading rates. Two different designs were tested, referred to as Design 1 (D1) and Design 2 (D2). The titanium structures in the implant specimens were additively manufactured by a powder-bed fusion process and subsequently embedded in a self-setting CaP material. D1 was conceptually representative of the clinically used implants. In D2, the titanium structure was simplified in terms of geometry in order to facilitate the manufacturing. The mechanical response of the implants was evaluated in quasi-static compression, and in impact using a drop-tower. Similar peak loads were obtained for the two designs, at the two loading rates: 808 ± 29 N and 852 ± 34 for D1, and 840 ± 40 N and 814 ± 13 for D2. A strain rate dependency was demonstrated for both designs, with a higher stiffness in the impact test. Furthermore, the titanium in the implant fractured in the quasi-static test (to failure) but not in the impact test (to 5.75 J) for D1. For D2, the displacement at peak load was significantly lower in the impact test than in the quasi-static test. The main difference between the designs was seen in the quasi-static test results where the deformation zones, i.e. notches in the titanium structure between the CaP tiles, in D1 likely resulted in a localization of the deformation, compared to in D2 (which did not have deformation zones). In the impact test, the only significant difference between the designs was a higher maximum displacement of D2 than of D1. In comparison with other reported mechanical tests on osteoconductive ceramic-based cranial implants, the CaP–Ti implant demonstrates the highest reported strength in quasi-static compression. In conclusion, the titanium structure seems to make the CaP–Ti implant capable of cerebral protection in impact situations like the one tested in this study. Graphical abstract: Image 1 Highlights: Mechanical tests of two CaP–Ti cranial implant designs were performed. In Design 2, less complex design features facilitated the additive manufacturing. The mechanical behaviour of the designs differed at quasi-static loading rates. The mechanical behaviour of the designs was similar in impact. The titanium structure of the implants provide protection at the level of impact tested.